A Collaborative and Reflective Academic Advanced Pharmacy Practice Experience - Roche, Victoria F. (American Journal of Pharmaceutical Education, 2011)
Objectives. To implement a co-precepted advanced pharmacy practice experience (APPE) focused on traditional pharmacy faculty and administrative responsibilities and reflection opportunities. Design. A multi-faceted, reflection-infused academic APPE was designed that exposed students to activities related to teaching, curriculum revision, scholarly writing, committee service, faculty role-modeling, mentorship and development, and school-level administrative decision-making. Assessment. Two students completed the APPE in the first 2 semesters it was offered (1 in spring 2010 and 1 in fall 2010). Formative and summative evaluations confirmed that the students achieved the APPE goals and viewed the experience as valuable, informative, and enjoyable as expressed both in reflective journal submissions and survey comments. Conclusion. Co-precepting by pharmacy faculty members primarily engaged in traditional faculty- and administration-related responsibilities can provide students with a robust learning experience that surpasses that which could be achieved by a single mentor.